Analisis kemampuan representasi matematis siswa ditinjau dari gaya belajar melalui model pembelajaran CORE - Saodah, Nursaodah; Mastur, Zaenuri; Suyitno, Amin (Tirtamath: Jurnal Penelitian dan Pengajaran Matematika, 2024)
The research was conducted to analyze the ability of mathematical representation in terms of learning styles through Connecting, Organizing, Reflecting, Extending (CORE). The ability of mathematical representation is very necessary for students, because with the ability of representation students can understand a concept and problem and turn it into a concrete form. This research is a mixed method research. The study was conducted at the Ciwaringin Islamic boarding school with subject class VII D as the experimental class and VII E as the control class. Data was collected through tests, questionnaires, and interviews. The results showed that the quality of learning through CORE on students' representational abilities was in the good category. Students with visual learning styles could use all indicators of mathematical representation to the maximum compared to students with auditory and kinesthetic learning styles